Community colleges worldwide investigating the global phenomenon - Wiseman, Alexander W., 1968- (Bingley, U.K. : Emerald, 2012)
This volume of the International Perspectives on Education and Society series comparatively examines various two-year and community college institutions worldwide. While these institutions are called by different names and may not all be structured the same around the world, their core mission remains consistently: to respond to the needs of their local community. Inspired by the German Volkshochschule, founded in 1844, this model is now throughout the U.S., Canada, Australia, India, South Africa, Thailand and other nations. While the community college is debatable and possibly controversial in and of itself, these institutions all serve the needs of their local communities by bridging the gap between academic and technical training with open and accessible learning. Students served by these institutions come from various socioeconomic backgrounds including age, race, culture, gender, and income levels. Two-year and community colleges adapt and institutionalize differently to meet various community needs, whether they provide students with technical training, the ability to transfer to four-year higher education institutions, remedial education or lifelong learning opportunities. This volume analyzes the ways this model has served and continues to serve communities in different international contexts for similar purposes.
Community colleges : where are they (not)? / Alexander W. Wiseman ... [et al.] -- Educational borrowing and the emergence of community college global counterparts / Rosalind Latiner Raby, Edward J. Valeau -- The Mexican idea of two-year university degrees : a model of opportunities and challenges / Gustavo Gregorutti -- Producing American citizens with 'global competence' : internationalization of higher education and the community college's contribution through English as a second language education of adult immigrants / Neriko Musha Doerr -- Indigenous rights and advanced capitalism in community colleges : the case of Nunavut Arctic College / Patricia Gaviria -- Post-secondary schools and the expansion of higher education in Poland : post-secondary vocational education in crisis? / Dobrochna Hildebrandt-Wypych -- Assisting workforce education in the Republic of Georgia / Ardith Maney -- The development of two-year technological colleges in Israel and its implications for stratification in higher education / Oren Pizmony-Levy ... [et al.] -- Implications of the community college model in Ethiopia / Akemi Yonemura -- The promise of the community college model in South Africa / C.C. Wolhuter -- Education access problems of migrant workers in manufacturing areas in China / Minghua Li, Henry Levin -- The evolving community college model in the socialist republic of Viet Nam / Cindy Epperson -- The Indian community college movement : an overview (1995-2011) / S. Xavier Alphonse -- The genesis and evolution of community colleges in Papua New Guinea / M.S. Joseph Antony Jacob -- The development of the community college system in Thailand / Tanom Intarakumnerd.
Includes indexes.
Keywords: Education -- Higher; Education -- Organizations & Institutions; Education -- Inclusive Education; Colleges of higher education; Adult education, continuous learning; Community colleges; Education, Higher